How to do (or not to do) ... a social network analysis in health systems research - Blanchet, K. (2012)
States that social network analysis can provide an appropriate and innovative paradigm for the health systems researcher, allow new analyses of the structure of health systems, and facilitate understanding of the role of stakeholders within a health system. Aims to demonstrate that seeing health systems as social networks can help to define the boundaries of health systems and understand the correlation between the health systems' performance and network parameters in low and middle-income countries (LMIC).